2023
DOI: 10.1044/2023_jslhr-22-00664
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Mental Health Difficulties in Young People With and Without Developmental Language Disorder: A Gene–Environment Interplay Study Using Polygenic Scores

Abstract: Purpose: Young people with developmental language disorder (DLD) have poorer mental health than those without DLD. However, not all young people with DLD are equally affected; some have more mental health difficulties than others. What explains these differences remains unclear. Method: Data from a community cohort study, the Avon Longitudinal Study of Parents and Children, were analyzed to investigate genetic and environmental influences on the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
1
9
0
1
Order By: Relevance
“…Collectively, the current descriptive findings align with studies reporting that nonverbal abilities, socioeconomic status, and health history are factors in quality of life for individuals with DLD (e.g., Conti-Ramsden et al, 2013;McGregor et al, 2023;Toseeb et al, 2023), as well as studies indicating quality of life challenges across physical, emotional, and educational domains (Eadie et al, 2018;Haukedal et al, 2023;Le et al, 2021). A preliminary aim for future research derived from the current findings, when considered alongside prior work, is to test how risk factors in particular quality of life challenges may vary depending on age and environmental demands (e.g., Orrego et al, 2023).…”
Section: Risk Factors and Quality Of Lifesupporting
confidence: 84%
“…Collectively, the current descriptive findings align with studies reporting that nonverbal abilities, socioeconomic status, and health history are factors in quality of life for individuals with DLD (e.g., Conti-Ramsden et al, 2013;McGregor et al, 2023;Toseeb et al, 2023), as well as studies indicating quality of life challenges across physical, emotional, and educational domains (Eadie et al, 2018;Haukedal et al, 2023;Le et al, 2021). A preliminary aim for future research derived from the current findings, when considered alongside prior work, is to test how risk factors in particular quality of life challenges may vary depending on age and environmental demands (e.g., Orrego et al, 2023).…”
Section: Risk Factors and Quality Of Lifesupporting
confidence: 84%
“…The current study cross-referenced previously reported candidate genes identified from studies of individuals with SLI and related phenotypes. Similarly, the genes identified from our family-based investigation provide additional targets for future studies of larger cohorts of unrelated individuals, which are the focus of many other groups studying the genetics of language [21][22][23], just as the foundational findings of linkage to chromosome 16q and 19q to SLI have been continually cross-referenced in results from both families and larger and larger cohorts of individuals with language and reading phenotypes [21,36,51,71,72].…”
Section: Implications Of Family-based Genetic Study For Understanding...mentioning
confidence: 89%
“…There is continued interest in strengthening our interdisciplinary approaches to speech and language impairments, especially in thinking about how speech-language pathologists can expand and use their knowledge of behavioral genetics in practice [20]. Additionally, there has been a push for utilizing larger cohorts of unrelated individuals and existing medical records for the genetic investigation of language traits [21][22][23]. Significantly, our study relies foremost on the sensitivity and specificity of the TEGI and the genetic relatedness of the participants and the power it may provide to the genetic investigation of SLI.…”
Section: Introductionmentioning
confidence: 99%
“…According to (Limaye, 2008), hearing impairment among adolescent girls complicated the issues such as bodily changes, peer relationships, autonomy, economic independence, marriage, family, and personal identity. The problem in speech and language has a great impact on the mental health (Toseeb, Vincent, Oginni, Asbury, & Newbury, 2023) of such girls that gradually promotes the social challenges while dealing at a wider community level.…”
Section: Impact Of Hearing Impairment On Adolescent Girls and Their M...mentioning
confidence: 99%